The Economic Burden of Non-Typhoidal Salmonella and Invasive Non-Typhoidal Salmonella Infection: A Systematic Literature Review - Sol Kim; Hyolim Kang; Jean-Louis Excler; Jerome H. Kim; Jung-Seok Lee (Vaccines, 2024)
Non-typhoidal Salmonella (NTS) infection and invasive non-typhoidal Salmonella (iNTS) infection cause a significant global health and economic burden. This systematic review aims to investigate the reported economic burden of NTS and iNTS infection, identify research gaps, and suggest future research directions. Data from PubMed and Embase databases up to April 2022 were reviewed, and articles were screened based on predefined criteria. Cost data were extracted, categorized into direct medical costs (DMCs), direct non-medical costs (DNMCs), and indirect costs (ICs), and converted into US dollars (year 2022). Data primarily originated from high-income countries (37 out of 38), with limited representation from Africa and resource-limited settings. For inpatients, DMCs were the primary cost driver for both NTS and iNTS illnesses, with estimates ranging from USD 545.9 (Taiwan, a region of China) to USD 21,179.8 (Türkiye) for NTS and from USD 1973.1 (Taiwan, a region of China) to USD 32,507.5 (United States of America) for iNTS per case. DNMCs and ICs varied widely across studies. Although study quality improved over time, methodological differences persisted. This review underscores the lack of economic data on NTS and iNTS in resource-limited settings. It also highlights the need for economic burden data in resource-limited settings and a standardized approach to generate global datasets, which is critical for informing policy decisions, especially regarding future vaccines.